Migration distance rather than migration rate explains genetic diversity in human patrilocal groups. - Marks, S; Levy, H; Martinez-Cadenas, C; Montinaro, F; Capelli, C (2012)
In patrilocal groups, females preferentially move to join their mate's paternal relatives. The gender-biased gene flow generated by this cultural practice is expected to affect genetic diversity across human populations. Greater female than male migration is predicted to result in a larger decrease in between-group differentiation for mitochondrial DNA (mtDNA) than for the non-recombining part of the Y chromosome (NRY). We address the question of how patrilocality affects the distribution of genetic variation in human populations controlling for confounding factors such as ethno-linguistic heterogeneity and geographic distance which possibly explain the contradictory results observed in previous studies. By combining genetic and bio-demographic data from Lesotho and Spain, we show that preferential female migration over short distances appears to minimize the impact of a generally higher female migration rate in patrilocal communities, suggesting patrilocality might influence genetic variation only at short ranges.